Genomic analysis and preclinical xenograft model development identify potential therapeutic targets for MYOD1‐mutant soft‐tissue sarcoma of childhood. Issue 1 (7th July 2021) - Ting, Michelle A; Reuther, Jacquelyn; Chandramohan, Raghu; Voicu, Horatiu; Gandhi, Ilavarasi; Liu, Meng; Cortes‐Santiago, Nahir; Foster, Jennifer H; Hicks, John; Nuchtern, Jed; Scollon, Sarah; Plon, Sharon E; et al.
Abstract: The myogenic differentiation 1 gene ( MYOD1 ) p.L122R somatic mutation was first discovered in a subset of clinically aggressive embryonal rhabdomyosarcomas and has since been described in both pediatric and adult spindle cell/sclerosing rhabdomyosarcomas. Relatively little is known about the clinical, molecular, and histopathological features of these tumors in children. In order to further characterize the genomic and clinical features of pediatric MYOD1 ‐mutant sarcomas, we evaluated a cohort of soft‐tissue sarcoma patients treated at Texas Children's Hospital. Tumor DNA was subjected to next‐generation panel sequencing and/or Sanger sequencing of the MYOD1 hotspot mutation. The MYOD1 p.L122R mutation was identified in six tumors, with a variant allele fraction greater than 0.8 in three cases, suggestive of loss of heterozygosity. One sclerosing rhabdomyosarcoma lacking the MYOD1 hotspot mutation was observed to have a MYOD1 copy number gain, also with evidence of loss of heterozygosity. Cancer gene panel sequencing revealed potentially targetable alterations in six of seven (86%) patients with MYOD1 alterations, including four patients with an alteration in the PI3K‐AKT pathway: two hotspot PIK3CA mutations and deletions in PTEN and TSC2 . On histopathologic review, MYOD1‐ altered tumors exhibited spindle and/or round cells and varying degrees of hyaline sclerosis. At last follow‐up, six patients had died of disease and the seventh progressed early and was subsequently lost to follow‐up. Both pre‐ and post‐therapy patient‐derived xenograft models were generated from one patient's tumor. These models were confirmed to harbor the MYOD1 and PIK3CA mutations seen in the primary tumor and were shown to be sensitive to PI3K/mTOR inhibition in vitro and in vivo . In conclusion, this study adds to recent reports describing the clinicopathologic and genomic features of MYOD1‐ altered soft‐tissue sarcomas in children, including dismal prognosis and potential molecular targets for therapy. The novel preclinical models developed will facilitate further biological and preclinical study of this rare and aggressive tumor. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.